Population pharmacokinetics of enrofloxacin and its metabolite ciprofloxacin in clinically diseased or injured Eastern box turtles (Terrapene carolina carolina), yellow‐bellied sliders (Trachemys scripta scripta), and river cooters (Pseudemys concinna). Issue 2 (12th February 2020) - Griffioen, John A.; Lewbart, Gregory A.; Papich, Mark G.
Abstract: Enrofloxacin is frequently administered to turtles in wildlife clinics during rehabilitation due to its wide spectrum of antibacterial activity and availability of injectable formulations. However, sufficient pharmacokinetic data to guide dosing are lacking. The objective of this study was to determine pharmacokinetic parameters of enrofloxacin and its active metabolite, ciprofloxacin, in chelonians presenting injured to a wildlife clinic. Thirty‐six Eastern box turtles (EBT, Terrapene carolina carolina ), 23 yellow‐bellied sliders (YBS, Trachemys scripta scripta ), and 13 river cooters (RC, Pseudemys concinna ) received a single subcutaneous injection of enrofloxacin at 10 mg/kg. Blood samples were collected between 0 and 240 hr postinjection. Pharmacokinetic parameters were determined using nonlinear mixed‐effects modeling (NMLE). Overall elimination half‐life (T½) was over 75 hr, and varied among species. T½ was 63 hr in EBT and 79 hr in YBS, which is longer than in previous reports. The volume of distribution (steady‐state) was 1.4 L/kg across turtle species, but highly variable—ranging from 0.4 L/kg in RC to 1.9 L/kg in YBS. Antibiotic concentrations were above a minimum inhibitory concentration value of 0.5 µg/ml for over 200 hr. These results indicate variable pharmacokinetic parameters for enrofloxacin among turtle species, which will help guide appropriate dosing protocols in injured turtles.